If you're seeing this message, it means we're having trouble loading external resources on our website.

If you're behind a web filter, please make sure that the domains *.kastatic.org and *.kasandbox.org are unblocked.

# Using the cosine double-angle identity

The cosine double angle formula tells us that cos(2θ) is always equal to cos²θ-sin²θ. For example, cos(60) is equal to cos²(30)-sin²(30). We can use this identity to rewrite expressions or solve problems. See some examples in this video. Created by Sal Khan.

## Want to join the conversation?

• Instead of doing Sin(A+B) and following these long formulas, couldn't we simply deduce any angles directly via Arcsin(y/h) and then add them together?

Eg: Sin(60 + Angle ABC) is simply Sin(60 + Arcsin(BC/AB)) •  The only problem I can find with this is that arc-functions are typically not introduced until after this point. Realistically, though, they could be introduced almost immediately after sines & cosines. I can't find a good, pedagogical reason why this happens.

Edit: Two years on, I can now see that I was talking about a special case. Your example of sin(60 + arcsin(BC/AB)) is actually making a simpl-ish case harder. I think what you were trying to end up doing is split the sine function over its respective inputs, i.e. sin(60) + sin(arcsin(ABC)), which does not work. The ONLY way to resolve trigonometric functions containing addition or subtraction is to use the formulas above (https://www.youtube.com/watch?v=ulQkjvHjWEc).
• In which video does he talk about why cos2x = cos^2 x = sin^2 x? • How are you supposed to do: cos²(θ)? Is it the same as cos(θ)²? • cos²(θ) is different with cos(θ)²
For example: θ = 60 degrees, then cos(θ) = 1/2
then cos²(θ) = (1/2)^2 = 1/4
and cos(θ)² = cos (60)(60) = cos 3600 degree = cos 0 degree = 1
3600 degree equals 10 full circles
• Please tell me the video cos(2*theta)=cos^2(theta)-sin^2(theta) • I don't think there is one yet. But you arrive at that trig identity by applying the sum formula. Watch:

1. First we apply the sum formula, cos(a+b) = cos(a) * cos(b) - sin(a) * sin(b):
cos(2*phi) = cos(phi + phi) = cos(phi) * cos(phi) - sin(phi) * sin(phi)
2. Now you can see that you are multiplying cos(phi) by itself and sin(phi) by itself. So,
cos(phi) * cos(phi) - sin(phi) * sin(phi) = cos^2(phi) - sin^2(phi)

What's interesting about this trig identity is that you can use it to calculate cos(phi) in terms of cos or sin, by applying the Pythagorean identity. So, you have two other trig identities derived from this one that are very useful. Sal could have also used any of them to solve the problem:

A You only know the cosine of the angle:
cos(2 * phi) = 2 * cos^2(phi) - 1
B. You only know the sine of the angle (you can actually calculate cos(2*phi) by just knowing the sine:
cos(2 * phi) = 1 - 2 * sin^2(phi)

In contrast, the sin of a product is not nearly as exciting:
sin(2*phi) = 2 * sin(phi) * cos(phi)
• There are three different double angle formulas for cosine:
cos2x = cos^2 x - sin^2 x
= 2cos^2 x - 1
= 1 - 2 sin^2 x
Do we have to memorize all formulas or if not, which one can be used for all scenarios? • You don't have to memorize all formulas but it helps to do so.
If you remember,
``1 = cos^2 x + sin^2 x``

So we have, `cos^2 x = 1 - sin^2 x` and `sin^2 x = 1 - cos^2 x`

If we replace `cos^2 x` in the first double angle formula `cos2x = cos^2 x - sin^2 x` with `1 - sin^2 x` we get:

`cos2x = 1 - 2 sin^2 x`

Similarly, if we replace `sin^2 x` in the first double angle formula `cos2x = cos^2 x - sin^2 x` with `1 - cos^2 x` we get:

`cos2x = 2 cos^2 x - 1`

Hope this helps.
• is cos^2(θ) the same as cos(θ)^2? If not then shouldn't the identity be cos(θ)^2? • Wait, this gives another explanation for cos(0) = 1. cos(a-b) = cos(a)cos(b) + sin(a)sin(b); cos(a-a) = cos(a)cos(a)+sin(a)sin(a) = cos²(a) + sin²(a) or [cos(a)]² + [sin(a)]²; cos(a-a) = cos²(a) + sin²(a), cos(0) = cos²(a) + sin²(a). And cos²(θ) + sin²(θ) = 1. Therefore, cos(0) = 1! • Are there any particular applications for sin(2a)=2sin(a)cos(a)? Is this less significant than cos(2a)=cos^2(a)-sin^2(a)?
(1 vote) • There are many applications from engineering, architecture and projects that involve design-to-specifications. The struts under a highway need to retrofitted to be a certain length, and currently the angle between the struts is such and such. To meet the requirement for stability under a certain earthquake, the angle cannot be greater than such and such, but to reach the other side of the road bed, the supports need to be lengthened by how much? The angle between two cross members is some measure, and in order to meet specs, it has to be increased, so how much longer do the rods need to be in order to create that angle? Even design of a chicken coop might be simplified if you can use calculations like these.
• I understand how the double angles work but how do I do triple angles? One of our homework questions is, cos(3x)cos(2x)-sin(3x)sin(2x) and it wants us to express it as a single trigonometric ratio. How do I do this?
(1 vote) • So I'm having problems with a question I got on a worksheet about Multiple-Angle Identities. I need to solve each equation for 0 ≤ theta ≤ 2pi, but I'm not sure about this one: -sin2θ = (√2)sinθ - 2sin2θ
Not sure if I'm going about this the right way but I substituted a double angle identity for sin2θ to get:
-(2sinθcosθ)= (√2)sinθ - 2(2sinθcosθ)
then I moved everything on one side to get:
0 = (√2)sinθ -(2sinθcosθ)
to get rid of the radical, I squared the right side but I'm not sure if it should look like this:
2sin^2θ - 4sin^2θcos^2θ
or:
2sinθ^2 - 4sinθ^2cosθ^2
or even:
2sin^2θ^2 - 4sin^2θ^2cos^2θ^2
Which is the right one? and am I doing this right so far?
Thanks.
(1 vote) • None of your suggestions are correct, and moreover, squaring both sides like this will not get rid of the radical.

Remember that if we square a quantity a+b, the result is (a+b)²
=(a+b)(a+b)
=a²+ab+ba+b²
=a²+2ab+b².

So if we square √2(sinθ)-2sinθcosθ, we get
2sin²θ-4√2sin²θcosθ+4sin²θcos²θ, which still has a √2 in it.

Instead of squaring, try factoring the expression on the right-hand side. You have a common factor of sinθ. So you can rewrite your equation as
0=(sinθ)(√2-2cosθ)

Since you have two things whose product is 0, you'll get solutions when either sinθ=0 or when √2-2cosθ=0. What does θ have to be for that to happen?